If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2(n + 1) = 2h Reorder the terms: 5 + 2(1 + n) = 2h 5 + (1 * 2 + n * 2) = 2h 5 + (2 + 2n) = 2h Combine like terms: 5 + 2 = 7 7 + 2n = 2h Solving 7 + 2n = 2h Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2n = -7 + 2h Combine like terms: 7 + -7 = 0 0 + 2n = -7 + 2h 2n = -7 + 2h Divide each side by '2'. n = -3.5 + h Simplifying n = -3.5 + h
| -4(2t-t)+5t=4t-2 | | 3(5x-7)-12x=-9 | | 6x-10=-8+8x | | x(a-b)=d+c | | 200=n+6(8+3n) | | -3/8x-4=1/8x-5 | | D=Ty | | 6*5+3=y | | 5g-2h=-5 | | 3x+9=7x-5 | | 122=9/5c+32 | | 4w+12(w-1)=36 | | 2(x+5)+3(x-5)=180 | | -5b=-8 | | 4x^2+8x=320 | | 21d-4=-67 | | -5(2t-3)+2t=8t-6 | | 8-2x+8+1=5x+5+1 | | 3*x-4=11 | | 3(4y-21)=7 | | 0.25x+7=0.33x-8 | | loge(x^2)-2=0 | | -2xy=-3 | | 15-.75z=13-.50z | | -6+3v+v=6 | | r+26-32r=-41 | | 8x^2-16x-8=0 | | -3(4t-5)+2t=6t-4 | | 2x+[5x(-2x-3x)]= | | 6x-10=2x-2 | | X=4x+8x | | 11-4n=17 |